A Type I Restriction Modification System Influences Genomic Evolution Driven by Horizontal Gene Transfer in Paenibacillus polymyxa - Chen, Ziyan; Shen, Minjia; Mao, Chengyao; Wang, Chenyu; Yuan, Panhong; Wang, Tingzhang; Sun, Dongchang (Frontiers in Microbiology, 2021)
Considered as a “Generally Recognized As Safe” (GRAS) bacterium, the plant-growth promoting rhizobacterium Paenibacillus polymyxa has been widely applied in agriculture and animal husbandry. It also produces valuable compounds that are used in medicine and industry. Our previous work showed the presence of restriction modification (RM) system in P. polymyxa ATCC 842. Here, we further analyzed its genome and methylome by using SMRT sequencing, which revealed the presence of a larger number of genes, as well as a plasmid documented as a genomic region in previous report. A number of mobile genetic elements (MGEs), including 78 insertion sequences, 6 genomic islands and 6 prophages, were identified in the genome. A putative lysozyme-encoding gene from prophage P6 was shown to express lysin which caused cell lysis. Analysis of the methylome and genome uncovered a pair of reverse-complementary DNA methylation motifs which were widespread in the genome, as well as genes potentially encoding their cognate type I restriction-modification system PpoAI. Further genetic analysis confirmed the function of PpoAI as a RM system in modifying and restricting DNA. The average frequency of the DNA methylation motifs in MGEs was lower than that in the genome, implicating a role of PpoAI in restricting MGEs during genomic evolution of P. polymyxa. Finally, comparative analysis of R, M and S subunits of PpoAI showed that homologs of the PpoAI system were widely distributed in species belonging to other classes of Firmicute, implicating a role of the ancestor of PpoAI in the genomic evolution of species beyond Paenibacillus.